When the Lophopids cross the Lydekker line from New Guinea, a new species for the genus Maana (Hemiptera: Fulgoromorpha) - Soulier-Perkins, Adeline; Stroiński, Adam (Zootaxa, 2013)
A new species of the genus Maana Soulier-Perkins, 1998 is described, M. keiensis Soulier-Perkins et Stroiński, sp. nov. The presence of this species on the Kei Islands is discussed from its historical biogeography point of view.